Pembelajaran Al-Quran Berbasis Edutainment - Abdul Halim; Dewi Anggraeni; Abdul Fadhil (Jurnal Studi Al-Qur'an, 2021)
This study aims to develop learning media in the form of Tahfizh cards in the learning process of memorizing Al-Quran with an edutainment approach. Tahfizh card is a learning medium in the form of cards that discusses learning to memorize the Qur'an, especially the short letters listed in juz 30 in a fun way that is suitable for children. The method used in this research is a research and development method using the Hanafin and Peck models. The techniques used in data collection were observation, interviews, and questionnaires. The results of this study indicate that the Tahfizh Card game learning media obtained value through the validation of media experts and theorists with the "very good" category of 96%. The edutainment approach in the process of learning the Qur'an and memorizing the Qur'an is very helpful for students, where it is a fun element that makes them not overwhelmed in the memorization process.